Przygotowanie danych w badaniach preferencji konsumentów metodami wyborów dyskretnych - Rybicka, Aneta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Discrete choice methods include varied experiments designs, varied procedures of generating factorial designs. The paper presents the process of choice experiments and data preparation to be used in next steps of research: full profiles choice experiments, partial profiles choice experiments and one-step and two-step procedures of generating factorial designs. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (19); 2007; nr 1180, s. 43-55